Implementation of Progressive Muscle Relaxation Therapy to Overcome & Prevent Complications in Hypertensive Degenerative Disease Kapasa Raya Makassar - Syaipuddin, Syaipuddin; Suhartatik, Suhartatik; Yasir Haskas, Yasir Haskas; Nurbaya, Sitti; Kasim, Jamila (International Journal of Public Devotion, 2024)
Hypertension is a disorder of the blood vessels that blocks the supply of oxygen and nutrients from the blood from reaching the tissues in the body that need it. Hypertension is a condition in which blood pressure increases beyond normal limits. Based on data obtained in the Working Area of the Kapasa Health Center, Tamalanrea District, Makassar City, hypertension is the second highest disease of the 10 highest diseases in the region. While Kapasa Raya sub-district Patients with hypertension predominantly experienced by the elderly usually have no complaints and only experience mild symptoms such as neck headaches, dizziness, irregular heartbeat, or often tired. This activity aims to determine the level of knowledge about hypertension in Kapasaraya District, Makassar City and the effectiveness of progressive muscle relaxation in the treatment and prevention of hypertension complications. The activity, which will be held on September 30, 2023, targets 20 people with high blood pressure in Kapasa Raya Village, Tamaranea District, Makassar City. There are two activities carried out are the provision of hypertension education materials and training on progressive muscle relaxation techniques. The provision of educational materials on hypertension topics is carried out with lecture and discussion techniques. Training in progressive muscle relaxation techniques is carried out directly.  The media used are PowerPoint slides and brochures on the LCD screen. The results of this activity provide information on the level of knowledge before carrying out hypertension education: less (75%), sufficient (25%). After the training there was a very significant increase in knowledge between less knowledge (20%) and sufficient knowledge (80%). The measurement results showed that progressive muscle relaxation exercises produced changes in systolic and diastolic blood pressure before and after exercise. Average systolic blood pressure 160.81 mmHg and diastolic 105.35 mmHg, as well as systolic blood pressure after exercise 153.32 mmHg and diastolic blood pressure 92.36 mmHg. The conclusion of this activity was that the level of knowledge of respondents increased after training and the decrease in blood pressure both systolic and diastolic changed after progressive muscle relaxation therapy.  The implication of this activity is that respondents and their families routinely perform progressive muscle relaxation exercises to reduce hypertension and prevent complications of hypertension